2018
DOI: 10.1186/s12969-018-0275-4
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of ultrasonography to detect inflammatory lesions and structural damage in juvenile idiopathic arthritis

Abstract: BackgroundMusculoskeletal Ultrasonography (MSUS) is an important tool for the clinical assessment in Juvenile Idiopathic Arthritis (JIA). The objective of this study was to evaluate the reliability of MSUS to detect elementary lesions: synovitis, tenosynovitis, cartilage damage and bone erosions in the wrist and metacarpal (MCP) joints of patients with JIA.MethodsThirty children in various subgroups of JIA according to ILAR criteria, were included in this cross-sectional study. Clinical data including painful,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 26 publications
1
22
0
3
Order By: Relevance
“…Reliability of the B mode US and PD US has been discussed in several recent studies. One study 11 concluded that more synovitis, tenosynovitis, cartilage damage and bone erosions could be detected via US compared to clinical examination and there has been good to excellent inter-and intraobserver reliability of US for the wrist and metacarpophalangeal joints. Furthermore, the superiority of SMI to PD in terms of diagnostic accuracy has been recently published without significant interobserver variability when measuring only synovial vascularity.…”
Section: Discussionmentioning
confidence: 99%
“…Reliability of the B mode US and PD US has been discussed in several recent studies. One study 11 concluded that more synovitis, tenosynovitis, cartilage damage and bone erosions could be detected via US compared to clinical examination and there has been good to excellent inter-and intraobserver reliability of US for the wrist and metacarpophalangeal joints. Furthermore, the superiority of SMI to PD in terms of diagnostic accuracy has been recently published without significant interobserver variability when measuring only synovial vascularity.…”
Section: Discussionmentioning
confidence: 99%
“…We stopped using the modified Sharp van der Heijde for pediatric assessment of joint damage [5] as it proved too difficult to uniformly score subtle changes in joint space narrowing, bony erosions and bone deformity, as was recognized previously [35]. Magnetic resonance imaging (MRI) and ultrasound (US) are suitable for monitoring disease activity for evaluating treatment response, and may also detect damage [36]. However, interpretation of MRI findings of the osteochondral domain in JIA patients is challenging due to characteristics of the growing skeleton, in particular in hand and wrist joints.…”
Section: Discussionmentioning
confidence: 99%
“…Because US was not provided for free after treatment for 24 weeks due to lack of sufficient funds, only a proportion of patients (n=39) underwent US detection after 24 weeks. US synovitis was defined as a joint that presented with greyscale abnormalities (joint effusion and hypertrophied synovium) or PD abnormalities according to several reports (7,12). The number of joints showing synovitis on US were calculated for further analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Ultrasonography (US), initially applied and recommended for evaluation of subclinical synovitis, disease activity, and treatment response in rheumatoid arthritis, has been introduced for JIA examination recently (7,8). US presents several advantages compared to other imaging technologies such as easy accessibility, fast imaging, dynamic feature, no exposure to radiation, and sedation-free (9).…”
Section: Introductionmentioning
confidence: 99%